2008
DOI: 10.1002/dvg.20404
|View full text |Cite
|
Sign up to set email alerts
|

Development of a gene‐trap vector with a highly sensitive fluorescent protein reporter system for expression profiling

Abstract: Combining high-content screening (HCS) with random gene-trap mutagenesis could be a powerful tool to investigate transcriptional networks, cell signaling, chemical genetics, and developmental processes. However, a critical limitation has been poor quantification of reporter expression per cell. To overcome this hurdle, we generated a variety of Gtx-based expression cassettes and re-evaluated translational enhancement of arrayed Gtx segments in tandem by HCS. We then modified the cassette into a new polyA trap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…pGTIV2 (ref. 56) was digested with ClaI and NsiI to remove an intervening sequence that contains one PvuII site, and ligated with a ClaI-NsiI linker (Invitrogen, Carlsbad, CA). This modified pGTIV2 was further digested with NotI and PvuII to obtain a cassette that contains Gtx motifs57, Venus 58 and polyadenylation signals (referred to as IVpA).…”
Section: Methodsmentioning
confidence: 99%
“…pGTIV2 (ref. 56) was digested with ClaI and NsiI to remove an intervening sequence that contains one PvuII site, and ligated with a ClaI-NsiI linker (Invitrogen, Carlsbad, CA). This modified pGTIV2 was further digested with NotI and PvuII to obtain a cassette that contains Gtx motifs57, Venus 58 and polyadenylation signals (referred to as IVpA).…”
Section: Methodsmentioning
confidence: 99%
“…First, we built the shRNA-expression vectors phH1CCP and phH1CRB ( Fig. 4A; (Tanaka et al, 2008); T, T2A (Szymczak et al, 2004) from the Rhox6 transgene or products of total Rhox6 transcripts (Fig. 3C).…”
Section: Constitutive Knockdown Of Rhox6 During Pgc Differentiation Imentioning
confidence: 99%
“…Total RNA extraction from ESCs and EBs, first-strand cDNA synthesis and semi-quantitative reverse transcriptase polymerase chain reaction (sqRT-PCR) assays were carried out essentially as described previously (Tanaka et al, 2008;Tanaka et al, 2010;Li et al, 2011). To determine the time course of PGC differentiation in EBs, 100 -200 EBs were pooled.…”
Section: Semi-quantitative and Quantitative Rt-pcrmentioning
confidence: 99%
“…In fact, several groups have performed expression microarray analyses at the single-cell level and have revealed populations of cells that differ in their transcript profiles (Crino et al, 1998;Chiang & Melton, 2003;Kurimoto et al, 2006;Ramos et al, 2006;Tang et al, 2010). Several studies, including ours, have found that well-maintained mouse ESC cultures consist of a small percentage of cells that show fluctuating expression levels of genes such as Dppa3 (Stella/Pgc7; Payer et al, 2006;Hayashi et al, 2008), Nanog (Chambers et al, 2007;Singh et al, 2007), Pecam1 (Furusawa et al, 2004;Furusawa et al, 2006), Rex1 (Toyooka et al, 2008) and Zscan4 (Falco et al, 2007;Zalzman et al, 2010), or genes associated with cell differentiation, such as Brachyury/T (Suzuki et al, 2006a;Suzuki et al, 2006b), Rhox6/9 (Carter et al, 2008), Tcf15 and Twist2 (Tanaka et al, 2008). These genes are either downregulated (Nanog and Rex1) or expressed (the rest) in about one-tenth of cells in culture as a steady state ( Fig.…”
Section: Transcriptional Heterogeneity In Pluripotent Stem Cellsmentioning
confidence: 75%